2017
DOI: 10.7150/jca.19383
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane Induced Apoptosis via Promotion of Mitochondrial Fusion and ERK1/2-Mediated 26S Proteasome Degradation of Novel Pro-survival Bim and Upregulation of Bax in Human Non-Small Cell Lung Cancer Cells

Abstract: Previous studies in our laboratory showed that sulforaphane (SFN) induced apoptosis by sustained activation of extracellular regulated protein kinases 1/2 (ERK1/2). However, the underlying mechanisms associated with SFN-induced apoptosis and downstream cascades which are modulated by ERK1/2 were not elucidated. Herein we demonstrated for the first time that alteration of mitochondrial dynamics contributed to SFN-induced apoptosis in human non-small cell lung cancer (NSCLC) cells. Reports showed that protein Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 33 publications
2
29
2
Order By: Relevance
“…The present study is the first to illustrate that inhibition of esophageal cancer cells using a CXCL antagonist may occur via inhibition of the PI3K/AKT signaling pathway. Previous studies have indicated that cell proliferation is strongly associated with cell apoptosis in the development of numerous types of cancer (31)(32)(33)(34)(35). In the present study, a reduction in cell proliferation was accompanied by increased apoptosis following treatment with UNBS5162, as determined by CCK-8 assays, flow cytometry and alterations in the expression of apoptosis-associated proteins.…”
Section: Discussionsupporting
confidence: 68%
“…The present study is the first to illustrate that inhibition of esophageal cancer cells using a CXCL antagonist may occur via inhibition of the PI3K/AKT signaling pathway. Previous studies have indicated that cell proliferation is strongly associated with cell apoptosis in the development of numerous types of cancer (31)(32)(33)(34)(35). In the present study, a reduction in cell proliferation was accompanied by increased apoptosis following treatment with UNBS5162, as determined by CCK-8 assays, flow cytometry and alterations in the expression of apoptosis-associated proteins.…”
Section: Discussionsupporting
confidence: 68%
“…ERK1/2 MAPK pathway is activated by different stimulus including growing factors, mechanical stress and so on (36). The activation of ERK1/2 is necessary for signal transduction, from cell membrane surface receptors to nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis can be induced by death receptor 5, activator protein 1, MAP kinases, or mithocondrial dysfunction, or by suppressing the mechanisms responsible for cellular survival, for example, inhibiting activation of the nuclear factor-kappa B [8,9]. Since sulforaphane has these multiple anticancer mechanisms, it is able to inhibit one or more pathways that contribute to malignant transformation and possesses cancer-preventive properties against different tumor diseases [10][11][12], including melanoma [13].…”
Section: Introductionmentioning
confidence: 99%